P05.14 Optimising trial recruitment in a meningioma trial using qualitative research methods: results from the ROAM / EORTC 1308 information study. (19th September 2018) - Jenkinson, M D; Sherratt, F C; Haylock, B J; Weber, D C; Young, B
Abstract: Background: ROAM/1308 is an international randomised controlled phase III trial comparing radiation to observation following complete surgical resection of atypical meningioma. We embedded a qualitative sub-study within ROAM/1308 with the aim of optimising patient recruitment. Material and Methods: Patients approached to participate in the ROAM trial and recruiting clinicians were enrolled into the sub-study in 11 UK sites. Audio-recorded recruitment consultation (n=30), and semi-structured interviews with clinicians (n=17) and patients (n=23), including decliners and consenters. Analysis of transcribed audio-recordings was informed by content and thematic analysis. Ethics approval was granted for the study. Results: Analysis identified areas where communication was problematic. Giving patients their pathology results immediately before discussing ROAM left them overwhelmed and unable to absorb trial information. Clinicians' presentation of the trial arms often lacked balance with a tendency to emphasise the negative aspects of radiotherapy whilst neglecting to discuss that radiotherapy may confer better disease control. Conversely the positive aspects of active monitoring (i.e. no additional treatment) were emphasised and the negative aspects of tumour recurrence were rarely discussed. Patients exhibited bias against radiotherapy citing concerns about side effects and this perception was rarely challenged by recruiting clinicians. Several patients viewed the prospect of radiotherapy as illogical, in part, due to earlier conversations with neurosurgeons who indicated further treatment was unnecessary following resection. Conclusion: Embedded qualitative studies can address barriers to recruitment in meningioma trials. We have amended the patient information leaflet and provided workshops and a webinar for healthcare professionals (surgeons, oncologists research nurses) to enhance communication about ROAM/1308. Subsequent recruitment consultations had a more balanced discussion of ROAM and clinicians felt more confident approaching patients about ROAM/1308. On going support will be provided to sites to assist them in implementing and maintaining changes in the recruitment consultation.